SEMANGAT BUSHIDO DALAM NOVEL “MUSASHI” KARYA EIJI YOSHIKAWA (SEBUAH KAJIAN BUDAYA BERDASARKAN PENDEKATAN ANALISIS ISI) - Haryono Haryono (Universitas Negeri Makassar, 2016)
Abstract. The Spirit of Bushido in “Musashi” novel by Eiji Yoshikawa. The present research deals with the Japanese cultural values that described in the novel